Achieving high capacity hybrid-cathode FeF3@Li2C6O6/rGO based on morphology control synthesis and interface engineering. Issue 26 (14th March 2018) - Lu, Chengyi; Dong, Chen; Wu, Haitao; Ni, Dan; Sun, Wang; Wang, Zhenhua; Sun, Kening
Abstract : The common high-capacity cathode Li2 C6 O6 shows poor cycling performance because of its dissolution in electrolytes. Abstract : The common high-capacity cathode Li2 C6 O6 shows poor cycling performance because of its dissolution in electrolytes. Using morphology control, spherical Li2 C6 O6 was prepared, and then combined with reduced graphene oxide and modified with an FeF3 coating. This interface engineering inhibited the dissolution of Li2 C6 O6, and also enhanced its cycling and rate performance.